Dimensions Affecting the Purchasing Behavior of Nepali Women - Thagunna, Karan Singh; Khanal, Garima (International Review of Management and Marketing, 2012)
The purpose of this study is to identify the various dimensions of buying behavior of Nepalese women while making purchasing decisions. A total of 100 women of different background were surveyed through a questionnaire consisting of 22 questions related to the buying behavior. Various factors such as Value Identification, Customer Service and Lifestyle are most influential for Nepalese women’s purchasing decisions. So, by providing, at affordable price, high value product that match the personality of the targeted women and by providing superior customer care, Nepalese women can be attracted easily. Besides these, price, brand awareness and accurate information also influence their buying behavior to a certain extent. Age also plays a role in the purchasing decisions she makes, since women of different age group behave differently while purchasing items for their homes, for their offices or for personal use. Difference in the demographic factors such as personal status, religious belief, occupation and income level however do not bring difference in the buying behavior of Nepalese women, in general. Keywords: Buying behavior; value identification; lifestyle; brand awareness JEL Classifications: M310; M370; M390